Aquatic Insect Drift and Water Quality of the River in Kubah National Park - Nur Fatihah, Abdul Malik (Universiti Malaysia Sarawak, (UNIMAS), 2015)
A study on the aquatic insects drift and water quality was conducted in the river of Kubah National Park. Samplings were conducted five times which were once in December 2014, thrice in February 2015 and once in March 2015. Drift samples and water quality measurements were taken at every three hours interval for a period of 24 hours during each sampling session. Drift samples were taken by using a Surber sampler. There were five water quality parameters measured in-situ which are pH, dissolved oxygen, temperature, turbidity and velocity and two water quality parameters measured ex-situ which are total suspended solids and also volume of water discharge by the sampler. A total of 313 individuals collected consisting of six orders of aquatic insects. Diptera was the most dominant group of aquatic insects in the drift sample followed by Plecoptera, Trichoptera, Ephemeroptera, Coleoptera and lastly Hemiptera. The total drift densities for the whole sampling period was 79.72 individuals per 100 m3 of volume filtered by the sampler and the highest drift density recorded was at 12.30 pm with 19.86 individuals per 100 m3 of volume filtered by the sampler. Analysis of Variance (ANOVA) showed no significant differences within each hour for each of the water quality parameters. Correlation Analysis by using Pearson Correlation showed that dissolved oxygen (r = - 0.54) and velocity (r = -0.50) have a strong correlation with drift densities. The drift pattern of these aquatic insects does not show a distinct diurnal pattern. Analysis by using paired t-test showed no significant difference between day and night drift samples (p = 0.839). The data gathered in this study is hoped to be useful for monitoring and managing the rivers of Kubah National Park in the future.